1985
DOI: 10.1002/j.1460-2075.1985.tb03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cells from embryonic chick dorsal root ganglia differentiate in vitro to neurons: biochemical and electrophysiological evidence.

Abstract: We have analyzed the appearance of neurons and glial cells in chick dorsal root ganglia during development. Neurons were identified by the presence of polysialogangliosides recognized by tetanus toxin (GD1b, GT1) or by the monoclonal antibody Q211 directed against polysialogangliosides containing four, five and six sialic acid residues. Glial cells were identified by the presence of 04 antigen. A population of undifferentiated cells, i.e., cells which express neither neuronal nor glial cell surface antigens, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 30 publications
(25 reference statements)
5
48
0
Order By: Relevance
“…To address the issue of whether Mk is derived from the neuronal or non-neuronal SG population, E7 SG were dissociated and neurons were immunopurified using the neuron-specific Q211 antibody (Rohrer et al, 1985;Rohrer and Thoenen, 1987;Zackenfels et al, 1995 The selective NB development in SG when compared with parasympathetic ganglia suggests that proliferation of parasympathetic neuron progenitors is not regulated by Alk signaling. Indeed, much lower Alk expression levels (8.3±0.1-fold, s.e.m.…”
Section: Forced Expression Of Constitutively Active Alk Mutations Asmentioning
confidence: 99%
“…To address the issue of whether Mk is derived from the neuronal or non-neuronal SG population, E7 SG were dissociated and neurons were immunopurified using the neuron-specific Q211 antibody (Rohrer et al, 1985;Rohrer and Thoenen, 1987;Zackenfels et al, 1995 The selective NB development in SG when compared with parasympathetic ganglia suggests that proliferation of parasympathetic neuron progenitors is not regulated by Alk signaling. Indeed, much lower Alk expression levels (8.3±0.1-fold, s.e.m.…”
Section: Forced Expression Of Constitutively Active Alk Mutations Asmentioning
confidence: 99%
“…Between E4 and E7, chick DRG contain progenitors whose initial survival is independent of NG,F (Ernsberger and Rohrer, 1988). As development proceeds, sensory neuron sur-viva1 can be enhanced by NGF, brain-derived neurotrophic factor (BDNF), and neurotrophin-3 (NT3) (Levi-Montalcini and Angeletti, 1968;Barde et al, 1980;Lindsay et al, 1985;Rohrer et al, 1985;Ernfors et al, 1990;Hohn et al, 1990;Maisonpierre et al, 1990).…”
Section: Stem Cell Factor Is a Neurotrophicmentioning
confidence: 99%
“…At all the stages studied here, ganglia contain indifferent cells (undifferentiated, neural progenitors), primitive neuroblasts, and intermediate neuroblasts (Pannese, 1974). It has been shown that neurons that have only recently developed from precursors are identifiable as SDB cells (Rohrer et al, 1985;Ernsberger and Rohrer, f 988;Wright et al, 1992). Like these authors, we, therefore, assumed that SDB cells were not axotomized by the isolation procedure and that they therefore grew their first neurites in culture.…”
Section: Quantitative Analysis Of Neurite Outgrowth In Culturementioning
confidence: 71%
“…To investigate further the possibility that newly formed neurons may behave differently from others in culture, measurements of neurite length were made from a morphologically distinct population of immature (SDB) neurons. These neurons had not been axotomized; in other words, they extended their first neurites in culture (Rohrer et al, 1985;Ernsberger and Rohrer, 1988;Wright et al, 1492). When these new neurons were taken from different segmental levels and cultured, statistically significant differences in the amounts of neurite outgrowth after 24 hours were observed.…”
Section: Segmental Independence Of Neurite Outgrowthmentioning
confidence: 99%
See 1 more Smart Citation